Libertines and Psychopaths. Penalization of homosexuality at the time of Czechoslo- vak Republic and the Czech medicine - Seidl, Jan (Theatrum historiae, 2013)
In this paper it is shown how during the interwar period the Czech medicine embraced in explaining of homosexuality the distinction between so-called “inborn” and “acquired” homosexuality (under the second designation was meant homosexual behavior of people, which were described by the physicians as straight from the nature) and how she gradually managed to establish this dichotomy as a valid category also in the theory and practice of criminal law. Persons accused in the interwar Czechoslovakia period of homosexual behavior were evaluated by the expert psychiatric inquiry, persons charged from the side of experts with the “inborn“ homosexuality could count with moderate or even no punishment, but the defendants with the “acquired“ homosexuality were seen as true and despicable criminals. At the same time, some reform-minded physicians actively participated in efforts to repeal the general criminalization of homosexuality in the Czechoslovak law - in this respect, however, their efforts were not crowned with success. This dual impact of medicine is analyzed for the purpose to decide whether and how the medicine managed to imprint its discourse on older categories developed by jurisprudence and practice of law. The conclusion is dedicated to an analysis of the impact of such development on the status of medicine among homosexuals.